2003
DOI: 10.1007/s15010-003-3048-y
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Rubella aboard a Ship of the German Navy

Abstract: Background: During May and June 1996, an outbreak of rubella occurred offshore aboard a ship of the German Navy. The outbreak spread among 330 crew members over a period of 9 weeks, ending 2 days after the ship's return. This is the first detailed epidemiological investigation of a rubella outbreak on a ship, describing temporal progression, clinical manifestations, immunization status and seroprevalence of the population exposed. Patients and Methods: Outbreak investigation using a questionnaire, health recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…It should be noted that the two highest attack rates (4% and 6%) were derived from sero-surveys after confirmed rubella outbreaks, which included asymptomatic cases (approx. 50% of cases in both studies); the highest attack (6%) was for a rubella outbreak on a Navy ship where no control measures were documented and the outbreak only ended after the ship’s return [3]. The mumps outbreak had a crew attack rate of 4%, and a crew attack rate of 2.4% was calculated from the data available for the measles outbreak in 2014 [31].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the two highest attack rates (4% and 6%) were derived from sero-surveys after confirmed rubella outbreaks, which included asymptomatic cases (approx. 50% of cases in both studies); the highest attack (6%) was for a rubella outbreak on a Navy ship where no control measures were documented and the outbreak only ended after the ship’s return [3]. The mumps outbreak had a crew attack rate of 4%, and a crew attack rate of 2.4% was calculated from the data available for the measles outbreak in 2014 [31].…”
Section: Resultsmentioning
confidence: 99%
“…For the 2014 measles outbreak on a cruise ship, as of 10 March 2014, there were 29 laboratory confirmed cases, 80% ( n = 23) of the cases were crew [3,31]. Twenty-three of the 968 crew (2.4%) and six of approximately 3352 passengers (0.2%) became infected with measles over a three-week period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jirous and Machula [13], have reported increasing incidence of rubella in the Czech Army. Ziebold et al [14], have reported an outbreak of rubella aboard a German ship having 12% susceptible sailors prior to the outbreak. The short review indicates that among militaries of different countries susceptibility varies, so does the vaccination policy.…”
Section: Discussionmentioning
confidence: 99%